Rethinking how DNA Methylation Patterns are Maintained - Jones, Peter A. (2009)
DNA methylation patterns are set up early in mammalian development and are then copied during the division of somatic cells. A long-established model for the maintenance of these patterns explains some, but not all, of the data that is now available. We propose a new model, which suggests that maintenance of DNA methylation relies not only on the recognition of hemi-methylated DNA by the methyltransferase DNMT1 but also on the localization of the DNMT3A and DNMT3B enzymes to specific chromatin regions containing methylated DNA.